Meta-Analysis and Bibliographic Study: Effectiveness of Biological and Chemical Agents in Controlling Spodoptera frugiperda Based on Mortality Rate from Scopus-Indexed Journals (2019-2024) - Pradiana, Maulani; Ramdhani, Fadhil (Edubiologica, 2023)
This meta-analysis and bibliographic study aims to compare the effectiveness of biological and chemical control methods against Spodoptera frugiperda, using the mortality rate percentage as the primary parameter. Data were pooled from studies indexed in Scopus from 2019 to 2024. Biological agents include species like Telenomus remus, Bacillus thuringiensis, and Trichogramma spp., while chemical agents include substances like emamectin benzoate, chlorpyrifos, and lambda-cyhalothrin. The research spans across multiple continents, highlighting significant contributions from China, Mexico, Brazil, Burkina Faso, Ethiopia, India, Indonesia, Pakistan, Ghana, Thailand, Cameroon, and Malawi, indicating a global effort to manage this pest. ANCOVA was employed to compare the efficacy of these control methods, controlling for covariates such as initial infestation levels and environmental conditions. The analysis confirmed the normality (sig. 0.51) and homogeneity of the data variances(sig.0.79), and linear relationships between covariates and the dependent variable were established. The final comparison revealed no significant difference between the effectiveness of biological and chemical agents in controlling Spodoptera frugiperda(sig. 0.279) This comprehensive assessment enhances the reliability and validity of the findings, providing insights for policymakers and agricultural practitioners to develop more effective pest management strategies and allocate resources efficiently.